THE TRANSLATION OF ENGLISH FIGURATIVE LANGUAGE IN MEAN GIRL MOVIE INTO INDONESIA - Ni Luh Putu Krisnawati (LITERA : Jurnal Bahasa Dan Sastra, 2017)
ABSTRACT  This research is focused on the English figurative language and its translation into Indonesiafound in the movie Mean Girl. The aims of this research are to find out the types of figurative language in English and its equivalence in Indonesia and to know the strategies used to translatethe English figurative language into Indonesian. The data of this study was taken from the movie Mean Girl released in the year of 2004. The data were collected through identifying thedialogues made by the character which are considered as figurative language and note taking thetranslation subtitle for the specific dialogue. The theory used for this research is the theory about the types of figurative language proposed by Henry Guntur Tarigan (2009) and the theoryproposed by Larson (1997) about translation strategies for figurative language. The findings shows that they are nine types of figurative language found in the Mean Girl movie, namelyantithesis, metaphor, simile, hyperbole, irony, paradox, sarcasm, euphemism and synecdoche andthe strategies used to translate the figurative language are translating the figurative language into its sense in TL and translating figurative language into figurative language in TL withoutreducing any meaning feature.  Key words: translation, figurative language, translation strategies.  ABSTRAK Penelitian ini difokuskan pada bahasa kiasan dalam bahasa Inggris dan terjemahannya kedalam bahasa Indonesia yang ditemukan dalam film Mean Girls. Tujuan dari penelitian ini adalah untuk mengetahui jenis bahasa kiasan dalam bahasa Inggris dan kesetaraan maknanyapada bahasa Indonesia dan untuk mengetahui strategi yang digunakan untuk menerjemahkan bahasa kiasan bahasa Inggris ke dalam bahasa Indonesia. Data penelitian ini diambil dari filmMean Girls yang dirilis pada tahun 2004. Data dikumpulkan melalui mengidentifikasi dialogyang dilakukan oleh karakter yang dianggap sebagai bahasa kiasan dan pencatatan subjudul terjemahan untuk dialog tertentu. Teori yang digunakan dalam penelitian ini adalah teoritentang jenis bahasa kiasan yang diusulkan oleh Henry Guntur Tarigan (2009) dan teori yang diusulkan oleh Larson (1997) tentang strategi penerjemahan untuk bahasa kiasan. Temuanmenunjukkan bahwa ada sembilan jenis bahasa kiasan yang ditemukan dalam film Mean Girls,yaitu antitesis, metafora, simile, hiperbola, ironi, paradoks, sarkasme, eufemisme dan synecdoche dan strategi yang digunakan untuk menerjemahkan bahasa kiasan adalahmenerjemahkan bahasa kiasan sesuai dengan maknanya pada TL dan menerjemahkan bahasa kiasan dalam bahasa kiasan di TL tanpa mengurangi apapun dalam fitur makna.